Durability of humoral immune responses to rubella following MMR vaccination. Issue 51 (3rd December 2020) - Crooke, Stephen N.; Riggenbach, Marguerite M.; Ovsyannikova, Inna G.; Warner, Nathaniel D.; Chen, Min-Hsin; Hao, Lijuan; Icenogle, Joseph P.; Poland, Gregory A.; Kennedy, Richard B.
Abstract: Background: While administration of the measles-mumps-rubella (MMR-II®) vaccine has been effective at preventing rubella infection in the United States, the durability of humoral immunity to the rubella component of MMR vaccine has not been widely studied among older adolescents and adults. Methods: In this longitudinal study, we sought to assess the durability of rubella virus (RV)-specific humoral immunity in a healthy population (n = 98) of adolescents and young adults at two timepoints: ~7 and ~17 years after two doses of MMR-II® vaccination. Levels of circulating antibodies specific to RV were measured by ELISA and an immune-colorimetric neutralization assay. RV-specific memory B cell responses were also measured by ELISpot. Results: Rubella-specific IgG antibody titers, neutralizing antibody titers, and memory B cell responses declined with increasing time since vaccination; however, these decreases were relatively moderate. Memory B cell responses exhibited a greater decline in men compared to women. Conclusions: Collectively, rubella-specific humoral immunity declines following vaccination, although subjects' antibody titers remain well above the currently recognized threshold for protective immunity. Clinical correlates of protection based on neutralizing antibody titer and memory B cell ELISpot response should be defined.